The role of essential fatty acids in cystic fibrosis and normalizing effect of fenretinide - Garić, Dušan; Dumut, Daciana Catalina; Shah, Juhi; De Sanctis, Juan Bautista; Radzioch, Danuta (Cellular and molecular life sciences, 2020)
Cystic fibrosis (CF) is the most common autosomal-recessive disease in Caucasians caused by mutations in the CF transmembrane regulator (CFTR) gene. Patients are usually diagnosed in infancy and are burdened with extensive medical treatments throughout their lives. One of the first documented biochemical defects in CF, which predates the cloning of CFTR gene for almost three decades, is an imbalance in the levels of polyunsaturated fatty acids (PUFAs). The principal hallmarks of this imbalance are increased levels of arachidonic acid and decreased levels of docosahexaenoic acids (DHA) in CF. This pro-inflammatory profile of PUFAs is an important component of sterile inflammation in CF, which is known to be detrimental, rather than protective for the patients. Despite decades of intensive research, the mechanistic basis of this phenomenon remains unclear. In this review we summarized the current knowledge on the biochemistry of PUFAs, with a focus on the metabolism of AA and DHA in CF. Finally, a synthetic retinoid called fenretinide (N-(4-hydroxy-phenyl) retinamide) was shown to be able to correct the pro-inflammatory imbalance of PUFAs in CF. Therefore, its pharmacological actions and clinical potential are briefly discussed as well.
Keywords: CFTR; Inflammation; esenciální mastné kyseliny; Cystic Fibrosis; fenretinid; Cystic fibrosis; Fenretinide; zánět; Animals; lidé; Fatty Acids, Unsaturated; cystická fibróza; Humans; zvířata; Fatty Acids, Essential; Lipids; antiflogistika; Anti-Inflammatory Agents; nenasycené mastné kyseliny; PUFAs